CORPORATE GOVERNANCE ATTRIBUTES AND EARNINGS QUALITY: EMPIRICAL STUDY OF INDONESIAN BANKS (2019-2023) - Liong, Jhun; Yessica, Tiffany; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2025)
Banking is one of the sectors that commonly attracts investors and is also one of the industries constantly scrutinized for the accuracy of its financial data, particularly profit. Profit helps investors determine whether the companies they are investing in will provide the necessary returns. Therefore, high-quality reported profit enables investors to make informed choices. Companies that understand that profit is a key component for investors often exploit information gaps between the firm and the investors, choosing to distort financial reports when times are tough. Thus, profit manipulation is closely tied to the principles of good corporate governance. Despite numerous cases and studies conducted, adequate information regarding the influence of good corporate governance on profit quality remains lacking. Therefore, further testing is necessary to examine the effect of good corporate governance—including managerial ownership, independent commissioners, audit committees, and the number of directors—as independent variables on profit quality, which serves as the dependent variable. The data was obtained from the financial statements of banking companies listed on the IDX from 2019 to 2023, using a non-probability sampling method specifically the purposive sampling technique. From the final dataset of 127 processed entries, it can be concluded that profit quality is influenced by the number of directors while managerial ownership, independent commissioners, and audit committees do not have an impact on profit quality.